How deep is the ocean? - Maric, Filip; Poto, Margherita Paola; Panieri, Giuliana; Peftieva, Olena (Septentrio Educational, 2023)
Focus: To gain an appreciation of ocean depth using ideas of scale and physical education. Learning objectives: With these TWO activities, pupils will begin to understand (and feel) how deep the ocean can be in relation to their own size and height. They will get a feeling of the difference between height (above ground) and depth (in relation to water). Key words: Height, (ocean) depth.